New records of Helminths in Reptiles from five states of Brazil - Quirino,T. F. (2018)
Abstract Forty five specimens representing nine species of reptile (Salvator merianae, Enyalius bilineatus, Amphisbaena alba, Xenopholis undulatus, Chironius fuscus, Helicops angulatus, Chironius flavolineatus, Erythrolamprus viridis and Crotalus durissus) collected in five Brazilian states were examined for helminths. Twelve helminth species were found as follow: nine Nematoda (Physaloptera tupinambae, Strongyluris oscari, Paracapillaria sp., Dracunculus brasiliensis, Physaloptera liophis, Serpentirhabias sp. 1, Serpentirhabias sp. 2, Serpentirhabias sp. 3 and Aplectana sp.), one Cestoda (Semenoviella amphisbaenia), one Trematoda (Paracotyletrema sp.), and one Acantocephala (Centrorhynchus sp.). Ten new host records and seven new locality records were reported.